2009
DOI: 10.1183/09031936.00169608
|View full text |Cite
|
Sign up to set email alerts
|

Iloprost for pulmonary vasodilator testing in idiopathic pulmonary arterial hypertension

Abstract: The aim of this study was to confirm the utility of aerosolised iloprost for identifying long-term responders to calcium channel blockers (CCBs) in patients with idiopathic pulmonary arterial hypertension (IPAH).While undergoing right heart catheterisation, 74 patients with IPAH sequentially received incremental infusions of adenosine and aerosolised iloprost. The effects of the two vasodilators on haemodynamic parameters were recorded. All acute responders identified by aerosolised iloprost were subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 30 publications
5
68
1
8
Order By: Relevance
“…While non-inferiority was shown for both agents in terms of efficacy, the iloprost was found to be safer with regard to side effects. In fact, only two out of the 74 patients in the study had side effects (a cough and hypotension) that could be attributed to this agent, [17] and in our study, no adverse effects were associated with iloprost.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…While non-inferiority was shown for both agents in terms of efficacy, the iloprost was found to be safer with regard to side effects. In fact, only two out of the 74 patients in the study had side effects (a cough and hypotension) that could be attributed to this agent, [17] and in our study, no adverse effects were associated with iloprost.…”
Section: Discussionmentioning
confidence: 39%
“…Thus, as an alternative to iNO, the use of inhaled iloprost has increased in recent years, [15,16] and many centers have started using it for vasoreactivity testing, particularly in adult patients. For example, a recent study by Jing et al [17] showed for the first time that aerosolized iloprost could be used for pulmonary vasoreactivity testing, and Opitz et al [18] found that inhaled iloprost demonstrates pulmonary selectivity in contrast to intravenous prostacyclin. In addition, it was found to be a more potent pulmonary vasodilator than iNO in studies conducted on adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary end-points included: time from randomisation to clinical worsening (defined as death, the first occurrence of hospitalisation for PAH or initiation of PAH targeted therapy decided by an independent panel of physicians) and change from baseline to week 24 in World Health Organization (WHO) functional class (an adaptation of the New York Heart Association classification [24]), Borg dyspnoea score (with 0 representing no dyspnoea and 10 maximal dyspnoea [23]), and haemodynamic parameters (mean pulmonary artery pressure, right atrial pressure, cardiac output and pulmonary vascular resistance) derived from right heart catheterisation. Haemodynamic parameters were measured as described previously [25]. Cardiac output was determined using the thermodilution technique or calculated according to the Fick method.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Diğer potansiyel pulmoner vazodilatör ajanlar İloprost inhalasyonu ve sildenafil gibi ajanlarla önemli boyutta pulmoner vazodilatör yanıt elde edilmiş olsa da PVT' de kullanımları için henüz yeterli klinik kanıt yoktur ve son güncel kıla-vuzlar henüz PVT için bu ajanları önermemektedir (1,2,20,29).…”
Section: Epoprostenolunclassified